Psychological risk factors for a first hamstring strain injury in soccer: a qualitative study - Baize, Diane; d’Arripe-Longueville, Fabienne; Piponnier, Enzo; Scoffier-Meriaux, Stéphanie (Frontiers in Sports and Active Living, 2024)
Introduction: Hamstring strain injuries (HSIs) remain one of the most burdensome injuries in soccer. Current recommendations to prevent sports injuries suggest the importance for coaches and medical staff to consider psychological and contextual risk factors and to specify them according to the injury type and context. HSI risk factors in soccer have been widely investigated, mainly from physiological and biomechanical perspectives. However, psychological and health-related risk factors are still unexplored. Therefore, the objective of this study was to determine the psychological and health-related risk factors for a first HSI in male competitive soccer. Method: Individual semi-structured interviews were conducted with ten male competitive soccer players, who had recently sustained a HSI. Based on multifactorial models of sports injury causation, soccer players’ individual, contextual, and situational risk factors at the time of their first HSI were investigated. Interviews were analyzed using thematic analysis with deductive and inductive approaches. Results: Individual psychological risk factors included common at-risk personality traits, obsessive passion for soccer with competitive motivational goals, strong athletic identity, and poor health literacy. The injured players were exposed to a controlling coaching style, with a fear of negative staff evaluations, and had recently experienced life stressors. They were injured during matches or overload periods and were highly engaged in the activity. Discussion: Previously injured soccer players exhibit a lack of perspective concerning the repercussions of their actions on their health. From a preventive viewpoint, these results suggest enhancing the players’ health literacy, supporting their autonomy, and moderating the controlling coaching style.